Development of Locomotor Skills in Children Aged 4-5 Years - Hasanah, Nur Lu’luul; Fatmawati, Fitri Ayu; Umairi, Mushab Al (STAI Miftahul Ula Nganjuk, 2024)
This study focuses on understanding the aspects of locomotor skill development in children aged 4-5 years at TK Dharma Wanita Persatuan Bengkololor Benjeng. The objective is to identify the causes of locomotor issues in